Multi-paradigm Java–Prolog integration in tuProlog - Denti, Enrico; Omicini, Andrea; Ricci, Alessandro (Science of computer programming, 2005)
tuProlog is a Java-based Prolog engine explicitly designed to be minimal, dynamically configurable, and support full and clean Prolog/Java integration. In this paper, we discuss the tuProlog approach to Prolog/Java multi-paradigm integration. After tuProlog motivations and requirements, we present some examples of bidirectional Prolog/Java integration and discuss the model and architecture of the tuProlog system. Then, we focus on the specific issue of the access to Java resources from tuProlog, discuss the essentials of its implementation, and compare it extensively with many other relevant related approaches and systems.